Resveratrol regulates neuro-inflammation and induces adaptive immunity in Alzheimer’s disease - Moussa, Charbel; Hebron, Michaeline; Huang, Xu; Ahn, Jaeil; Rissman, Robert A.; Aisen, Paul S.; Turner, R. Scott (Journal of neuroinflammation, 2017)
Treatment of mild-moderate Alzheimer's disease (AD) subjects (N = 119) for 52 weeks with the SIRT1 activator resveratrol (up to 1 g by mouth twice daily) attenuates progressive declines in CSF Aβ40 levels and activities of daily living (ADL) scores. For this retrospective study, we examined banked CSF and plasma samples from a subset of AD subjects with CSF Aβ42 <600 ng/ml (biomarker-confirmed AD) at baseline (N = 19 resveratrol-treated and N = 19 placebo-treated). We utilized multiplex Xmap technology to measure markers of neurodegenerative disease and metalloproteinases (MMPs) in parallel in CSF and plasma samples. Compared to the placebo-treated group, at 52 weeks, resveratrol markedly reduced CSF MMP9 and increased macrophage-derived chemokine (MDC), interleukin (IL)-4, and fibroblast growth factor (FGF)-2. Compared to baseline, resveratrol increased plasma MMP10 and decreased IL-12P40, IL12P70, and RANTES. In this subset analysis, resveratrol treatment attenuated declines in mini-mental status examination (MMSE) scores, change in ADL (ADCS-ADL) scores, and CSF Aβ42 levels during the 52-week trial, but did not alter tau levels. Collectively, these data suggest that resveratrol decreases CSF MMP9, modulates neuro-inflammation, and induces adaptive immunity. SIRT1 activation may be a viable target for treatment or prevention of neurodegenerative disorders. ClinicalTrials.gov NCT01504854.